Monoclonal antibody precision therapy targeting inflammation for bipolar disorder: a narrative review - Shijin Wu; Yuyang Zhou (SAGE Publishing, 2024)
Bipolar disorder (BD) is a severe mental disorder with various hypotheses regarding its pathogenesis. This article provides a summary of numerous studies on the variations in inflammatory cytokine levels in patients with BD and the effects of treatment with antipsychotics, mood stabilizers, and antidepressants on these levels. In addition, patients with autoimmune diseases who use anti-inflammatory monoclonal antibodies experience symptoms, such as depression, anxiety, and insomnia. These pieces of evidence suggest a potential association between immune inflammation and BD and offer new possibilities for therapy. Building upon this relationship, the authors propose an innovative approach for treating BD through individualized and precise therapy using anti-inflammatory monoclonal antibody drugs. To support this proposal, the authors compile information on pharmacological effects and relevant studies, including trials of various anti-inflammatory therapeutic monoclonal antibody drugs (e.g. infliximab, tocilizumab, and canakinumab) for the potential treatment of BD and its associated side effects in psychiatry. The authors categorize these anti-inflammatory monoclonal antibody drugs into levels I-IV through a comprehensive analysis of their advantages and disadvantages. Their potential is examined, and the need for further exploration of their pharmaceutical effects is established.